3-Hydroxyanthranilic acid oxygenase-containing astrocytic processes surround glutamate-containing axon terminals in the rat striatum - Roberts, RC (J Neurosci, 1995)
Glutamate, the major transmitter of the corticostriatal pathway, is present in abundance in the striatum. 3-Hydroxyanthranilic acid oxygenase (3HAO) is the biosynthetic enzyme for quinolinic acid, an endogenous agonist of the NMDA glutamate receptor subtype and a potent neurotoxin. In order to explore the anatomical basis of possible functional interactions between glutamate and quinolinic acid in the rat striatum, pre- and postembedding immunocytochemical methods were used to localize 3HAO immunoreactivity (-i) and glutamate-i at the electron microscopic level. In accordance with previous light microscopic and biochemical studies, 3HAO-i was detected exclusively in astrocytes throughout the striatum. Notably, 3HAO-i was present in fine- caliber glial processes that often surrounded or abutted synaptic profiles, both asymmetric and symmetric. Glutamate-i was heavily deposited (3–13-fold higher gold particle density than tissue average) in axon terminals forming asymmetric synapses with spines and, occasionally, dendrites. In contrast, terminals forming symmetric synapses, dendrites, neuronal somata, and glial cells contained significantly less labeling than terminals forming asymmetric synapses. In double-labeled material, 3HAO-i was observed in glial processes that partially surrounded or were adjacent to glutamate-labeled terminals forming asymmetric synapses. 3HAO-labeled glial processes were also adjacent to unlabeled terminals forming symmetric synapses. Since quinolinic acid is known to enter the extracellular compartment readily, these results suggest that astrocytic quinolinic acid may participate in the regulation of glutamatergic neurotransmission in the rat striatum.